(untitled) (Journal of Forensic Medicine & Toxicology, 2012)
This paper presents a 17 years old female with recurrent chest infections with idiopathic etiology presenting as polysplenia syndrome with cardiovascular manifestations. In addition to multiple spleens, the thoracic findings included a ‘left’ sided inferior vena cava with both azygous and hemiazygous continuation. The cardiovascular findings revealed an anomalous origin of right subclavian artery along with common origin for carotid arteries.